Effect of livelihood diversification on poverty reduction among members of cooperative rural farmers in anambra state, nigeria - Akwaekwe; Christian Ikechukwu; Agbasi; Obianuju Emmanuela (Journal of Management and Science, 2022)
This study investigated the effect of livelihood diversification on poverty reduction among members of cooperative rural farmersin Anambra State, Nigeria. The specific objectives are to ascertain the extent to which craftsmanship, paid labour, trading,service delivery and asset income have influenced poverty reduction among members of cooperative rural farmers in Anambra State. The study was a descriptive survey on a sample 142 respondents. Data for the study were obtained using a structured questionnaire and was subsequently analyzed using frequency tables, percentages and regression technique of the ordinary least square. Findings revealed that craftsmanship, Paid labour, service delivery and asset income have significant influence on poverty reduction among members of cooperative rural farmers in Anambra State. The study concludes that four out of the five regression coefficient - craftsmanship, paid labour, trading and asset income - significantly influenced poverty reduction among members of cooperative rural farmers in Anambra State, Nigeria. Service delivery was not significant but it had positive relationship with poverty reduction among members of cooperative rural farmers in Anambra State thus suggesting inadequate service delivery businesses among members of cooperative societies. Based on the findings of the study, the following recommendations are made: Cooperative societies should educate members on livelihood diversification craft engagements to help lift their members from poverty. Cooperative societies should train their members on skills that will enable them seek rewarding paid labour as a means of diversifying their livelihood strategies. The societies should help members obtain adequate affordable credit to go into meaningful trading. This is because trade was found to significantly reduce poverty among members of cooperative rural farmers in Anambra State. Members of cooperative should consider going into service delivery business like financial services which is a trending business today. Apart from commercial building for renting and receiving royalty from farm land, members of cooperative should consider investment in Stocks and securities, real estate, franchise and crypto businesses.